Analysis Of Factors Influencing The Decision Of Sugarcane Farmers To Use The Services Of Financial Institutions Savings And Loan Cooperatives Independent Business Partners In Semboro Jember District - Rohman Prayogi (Journal of Social Research, 2024)
The aim of this research is to find out what factors influence sugar cane farmers in making decisions to use the services of the financial institution KSP Mitra Usaha Mandiri Semboro. And to find out what factors are most dominant in sugar cane farmers' decision to use the services of the financial institution KSP Mitra Usaha Mandiri Semboro. The factors in this research are reduced from service quality items which consist of the dimensions of Reliability, Responsiveness, Assurance, Empathy and Physical Evidence. The type of research used in this research is explanatory research. This research uses a quantitative descriptive method approach. The sample in this study was sugar cane farmers who were partners with PG Semboro and also KSP Mitra Usaha Mandiri, totaling 89 respondents. The sampling technique used was purposive sampling. The results of the research show that the factors that influence sugar cane farmers in making decisions to use the services of the financial institution KSP Mitra Usaha Mandiri Semboro are responsiveness, guarantees, quality and service as well as attention or empathy. Responsiveness is the most dominant factor taken into consideration by farmers in deciding to use financial services from KSP Mitra Usaha Mandiri Semboro, Jember Regency.